Intracerebroventricular Injection of Ghrelin Induces Sleep-Like Behavior in Neonatal Chicks - Tetsuya Tachibana; Atsushi Ohgushi; Mitsuhiro Furuse (The Journal of Poultry Science, 2001)
Ghrelin, a novel growth hormone (GH)-releasing acylated peptide, is recently isolated from rat stomach. This peptide stimulates the release of GH from the anterior pituitary through the GH secretagogue receptor and feeding in the rat. However, intracerebroventricular (ICV) injection of rat ghrelin inhibited feeding of chicks under both ad libitum feeding and fasting conditions (Furuse et al., 2001). Thus, we have investigated the behavioral changes by ghrelin with special reference to sleep-like behavior of the neonatal chick in two experiments. Four behavioral categories were distinguished and scored as follows: 1, standing with eyes open; 2, sitting with eyes open; 3, standing with eyes closed; and 4, sitting motionless with head drooped (sleeping posture). Firstly, ICV injection of 0, 1.25, 2.5 and 5μg of ghrelin was done to ad libitum fed birds. Secondly, several doses (0, 0.5, 1 and 2μg) of ghrelin were injected ICV into chicks previously deprived of food for 3h. In both experiments, scores of ghrelin treated birds were higher than those of control birds. These results suggest that one of the central roles of ghrelin in the neonatal chick is induction of sleep.